The rationality behind performance of routine lumber puncture in simple febrile seizure in 6-18 months old children - Ali, Sarful; Datta, Kalpana; Karmakar, Balai Chandra (International Journal of Contemporary Pediatrics, 2021)
Background: Pediatrics seizures can be either due to febrile seizure or underlying serious infection such as meningitis. It is important to rule out meningitis in children presenting with fever and seizure. The aim of the study was conducted to assess the necessity of routine lumber puncture and to determine the incidence of meningitis among children aged 6 to 18 months presenting with first episode of febrile seizure. Methods: This prospective observational study was conducted among 47 children with first episode of simple febrile seizure presenting to emergency in Medical College Kolkata, West Bengal from April 2018 to September 2019. Results: Total 47 children were studied among 32 (68%) children were between 6-12 months and 15 (32%) were between 12-18 months of age. Only 1 child (2.1%) diagnosed as meningitis. Clinically 7 children (14.9%) showed signs of sepsis and meningitis like picture and 6 children (12.8%) were in 6-12 months of age and only 1 child (2.1%) was in 12-18month of age. Only 1 child in 6-12 months of age showed CSF positive and all other CSF studies were within normal limit. A significant association was seen between age group and hyponatremia and family history of febrile seizure (p<0.05). There was no statically significant between clinical diagnosis and CSF results (p=0.15). Conclusions: The risk of meningitis in children presenting with simple febrile seizure between 6-18 months of age is very low, specially in 12-18 months of age. Therefore, current guidelines regarding lumber puncture in simple febrile seizure should be reconsidered.